Pengaruh Kualitas Pelayanan Dan Penetapan Harga Terhadap Loyalitas Konsumen Pada Hotel Aryaduta Manado - Kharies Dwi Manossoh Purnomo; Fernando Victor Dotulong; Nelfiani Nancy Kaurow; Nolvy Ruata; Fiany Laloan (Master Manajemen, 2025)
This study is about the influence of service quality and pricing on consumer loyalty at the Aryaduta Manado Hotel. The purpose of this study is to determine the influence of (1) service quality on consumer loyalty, (2) the influence of pricing on consumer loyalty, (3) service quality and pricing on consumer loyalty. The method used in this study is quantitative in the form of a survey using a questionnaire as a data collection tool. The sampling technique uses the Slovin formula, with a population of 40 taken from consumers at the Aryaduta Manado Hotel with a precision of 0.05 or 5%. The analysis tools used are correlation analysis and multiple linear regression analysis. While the results of the simultaneous correlation coefficient value r = 0.443, indicating that service quality and pricing have a fairly strong and significant relationship to increasing consumer loyalty at the Aryaduta Manado Hotel. The determination coefficient value r2 = 0.196 indicates that the increase in consumer loyalty at the Aryaduta Manado Hotel where 19.3% is influenced by service quality and pricing together, while the remaining 80.7% is influenced by other factors. Therefore, management and employees need to pay attention to service quality and pricing to increase customer loyalty at the Aryaduta Manado Hotel.